1996
DOI: 10.1002/jbmr.5650110915
|View full text |Cite
|
Sign up to set email alerts
|

Strontium distribution and interactions with bone mineral in monkey iliac bone after strontium salt (S 12911) administration

Abstract: The analysis of the interaction of strontium (Sr) with bone mineral is of interest because a new agent containing Sr (S 12911) has shown positive effects on bone mass in various animal models of osteoporosis and is currently being developed for preventive and curative treatment of postmenopausal osteoporosis. Iliac bone samples were obtained from 20 male monkeys: 4 untreated control animals, 12 animals sacrificed at the end of a 13-week treatment with high dose levels of S 12911 (750, 275, or 100 mg/kg/day ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
2
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(111 citation statements)
references
References 14 publications
9
96
2
4
Order By: Relevance
“…We also observed slight release of Sr ions from the experimental adhesive used in group 2. It has been confirmed that Sr ions are effective in inducing calcification during bone formation [33][34][35][36] . In addition, Ammann reported that Sr ions also promoted differentiation from pre-osteoblasts into osteoblasts and controlled the action of osteoclasts, thus promoting bone formation 37) .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We also observed slight release of Sr ions from the experimental adhesive used in group 2. It has been confirmed that Sr ions are effective in inducing calcification during bone formation [33][34][35][36] . In addition, Ammann reported that Sr ions also promoted differentiation from pre-osteoblasts into osteoblasts and controlled the action of osteoclasts, thus promoting bone formation 37) .…”
Section: Discussionmentioning
confidence: 88%
“…Si and F ions, in particular, are known as strong inducers of remineralization of the dentin matrix [29][30][31][32] . It is also well known that B and Sr have osteogenic potential [33][34][35][36][37][38] . Sr promotes differentiation of pre-osteoblasts into osteoblasts [33][34][35][36][37] , and it inhibits osteoclast differentiation and activity 37) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory studies, the amount of strontium incorporated into the skeleton of animals is believed to directly reflect the amount available from the diet and environment, i.e. it is dose-dependent (Boivin et al 1996, Dahl et al 2001, Pan et al 2009, Price et al 1986), as there are no known homeostatic mechanisms that specifically regulate levels of such non-nutrients (Parker and Toots 1980).…”
Section: Accepted For Publication In the Annals Of Human Biology 2010mentioning
confidence: 99%
“…Either scenario will attenuate the input signal obtained from bovine enamel and in migratory cattle will result in strontium isotope ratios that are a mixture of two or more end-members rather than discrete ratios characteristic of a 19 single lithology. How long before a change in residence becomes evident within the enamel will depend on various biological factors but because strontium is not an essential element and the amount deposited in skeletal tissue reflects how much is ingested, the averaging process will also be sensitive to the relative concentrations of strontium and calcium in the diet (Knight et al 1967;Boivin et al 1996;Meiggs 2007). If the strontium concentrations of the enamel are very similar, as found in the tooth in this study, it appears that the tissue may take a year to fully reflect a change from one locality to another.…”
Section: Implications For Long-term Averaging Of the Measured Signalmentioning
confidence: 99%